A fully bio-based gel adhesive with temperature-responsive bonding properties and a preparation method thereof
By blending gelatin and sodium alginate, and using "salt-out" and metal coordination technology to form a zinc-sodium alginate polymer phase, a full bio-based gel adhesive with high toughness and temperature-responsive adhesive was prepared, solving the problem of insufficient mechanical properties and self-adhesion of existing hydrogels.
Patent Information
- Application Number
- CN202410228255.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-02-29
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2044-02-29
AI Technical Summary
The existing hydrogels have shortcomings in mechanical properties and self-adhesion, and most of them are synthesized from petroleum-based raw materials, which have defects such as cumbersome preparation process, poor biocompatibility, non-renewable, and difficult to degrade.
The gel was prepared by blending gelatin and sodium alginate, and the aggregation state of the polymer chain was regulated through the "salt-out" effect, combined with the introduction of Zn2+ to form a zinc-sodium alginate polymer phase, and a full bio-based gel adhesive with a phase separation structure was constructed.
The prepared gel can be stretched to 5 times the initial length under uniaxial stretching conditions, and the tear energy can reach 6374.67J/m2, and has temperature-responsive bonding properties. The bonding strength with the zinc sheet reaches 438kPa after heating at 60°C for 5 minutes, which significantly improves the mechanical properties and self-adhesion of the hydrogel.
Smart Images

Figure CN118240526B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of bio-based gel adhesives, and specifically relates to a full-bio-based gel adhesive with temperature-responsive bonding properties and a preparation method thereof. Background Art
[0002] Hydrogel is an extremely hydrophilic three-dimensional network structure gel formed by physical or chemical crosslinking. Due to the existence of the cross-linked network, hydrogel can swell and retain a large amount of water. This property is very similar to biological tissue, so it is widely used in electronic devices, environmental engineering, biomedicine and other fields.
[0003] At present, most hydrogels are synthesized mainly from petroleum-based raw materials, which have defects such as complicated preparation process, poor biocompatibility, non-renewable and difficult to degrade. As the concept of sustainable development has become more popular, renewable and degradable biomass resources have received more and more attention and have become one of the raw materials with the most development potential for hydrogels.
[0004] At present, people have prepared a series of bio-based hydrogels using cellulose, chitosan, sodium alginate, etc. as the main body, but they have defects such as poor toughness, complex preparation process, and the use of toxic substances as cross-linking agents, which limits their scope of use. Summary of the invention
[0005] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.
[0006] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.
[0007] Therefore, the purpose of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing a fully bio-based gel adhesive with temperature-responsive bonding properties.
[0008] In order to solve the above technical problems, the present invention provides the following technical solutions: a method for preparing a fully bio-based gel adhesive with temperature-responsive bonding properties, comprising:
[0009] The gelatin is heated to obtain a gelatin solution;
[0010] The sodium alginate is heated and stirred to obtain a sodium alginate solution;
[0011] The gelatin solution and the sodium alginate solution are mixed, the macromolecular chains of the gelatin and the sodium alginate are entangled, and after being stirred evenly, the mixture is poured into a mold and refrigerated to obtain a gel;
[0012] The gel was immersed in a mixed solution of ammonium sulfate and lithium sulfate, and NH4 + 、SO4 2- , Li + The "salting out" effect reduces the solubility of gelatin, causing the gelatin macromolecular chains to aggregate and entangle. During the "salting out" process, water molecules are discharged from the macromolecular chains, and a large number of hydrogen bonds are formed between the gelatin molecular chains, thereby forming crystal domains.
[0013] The obtained gel is then immersed in a mixed solution of ammonium sulfate, lithium sulfate, and zinc acetate. 2+ Under the action of zinc-sodium alginate, a polymer phase is formed through metal coordination, thereby obtaining a gelatin-sodium alginate gel adhesive with gelatin as the crystalline phase and zinc-sodium alginate as the polymer phase.
[0014] As a preferred embodiment of the preparation method of the present invention, the mass concentration of the gelatin solution is 20-30%.
[0015] As a preferred embodiment of the preparation method of the present invention, the mass concentration of the sodium alginate solution is 2-4%.
[0016] As a preferred embodiment of the preparation method of the present invention, the gelatin solution and the sodium alginate solution are blended, wherein the mass ratio of the gelatin solution to the sodium alginate solution is 1:0.5-1.
[0017] As a preferred embodiment of the preparation method of the present invention, the mixture is poured into a mold and refrigerated, wherein the refrigeration temperature is 2 to 4° C. and the gel time is 1 to 2 hours.
[0018] As a preferred embodiment of the preparation method of the present invention, the pH value of the precursor obtained by mixing the gelatin solution and sodium alginate is 5-7.
[0019] As a preferred embodiment of the preparation method of the present invention, the gel is immersed in a mixed solution of ammonium sulfate and lithium sulfate, wherein the concentration of ammonium sulfate in the mixed solution is 30wt%, the concentration of lithium sulfate is 1mol / kg, and the immersion time is 10 to 12h.
[0020] As a preferred embodiment of the preparation method of the present invention, the obtained gel is immersed in a mixed solution of ammonium sulfate, lithium sulfate and zinc acetate, wherein the concentration of ammonium sulfate in the mixed solution is 30wt%, the concentration of lithium sulfate is 1mol / kg, and the concentration of zinc acetate is 3mol / kg, and the immersion time is 12 to 24h.
[0021] Another object of the present invention is to overcome the deficiencies in the prior art and provide a product prepared by a method for preparing a fully bio-based gel adhesive having temperature-responsive bonding properties, wherein: the gel adhesive can be stretched to 5 times its initial length under uniaxial stretching conditions, and the tear energy can reach 6374.67 J / m 2 , has temperature-responsive bonding properties, and the bonding strength with the zinc sheet reaches 438kPa after heating at 60°C for 5 minutes.
[0022] Another object of the present invention is to overcome the deficiencies in the prior art and provide an all-biobased gel adhesive for use in flexible wearable materials and biomedical engineering.
[0023] Beneficial effects of the present invention:
[0024] (1) The present invention prepares hydrogels by blending. Compared with the traditional hydrogel preparation method, the preparation method of the present invention is simple and mild; compared with the general bio-based hydrogel (tear energy ~100 J / m 2 , bonding strength does not exceed 10kPa) has higher tear energy and bonding strength, can be stretched to 5 times the initial length under uniaxial tension conditions, and the tear energy can reach 6374.67J / m 2 ; It has temperature-responsive bonding properties. After heating at 60°C for 5 minutes, the bonding strength with the zinc sheet reaches 438kPa, which helps to improve the current problems of poor mechanical properties and insufficient self-adhesion of hydrogels.
[0025] (2) The present invention provides a method for preparing a fully bio-based gel adhesive with temperature-responsive bonding properties, which regulates the aggregation state of polymer chains through the "salting out" effect. During the "salting out" process, water molecules are discharged from the gelatin macromolecular chains, and a large number of hydrogen bonds are formed between the gelatin molecular chains, thereby forming crystallization domains; by Zn 2+ The introduction of makes the sodium alginate macromolecular chain metal coordinated to form a zinc-sodium alginate polymer phase, thereby constructing a new all-biobased gel adhesive with a phase separation structure. In the gelatin-sodium alginate polymer network, the polymer phase is used to transfer stress and dissipate energy, and the crystal domain is used to pin cracks, thereby obtaining a gel adhesive with high toughness; at the same time, when used for bonding, the gelatin crystal domain softens under high temperature, increasing the contact area with the adherend, and forming a large number of hydrogen bonds between the adhesive layers, generating strong binding energy, thereby improving the interfacial force between the gel adhesive and the adherend; the cross-linked zinc-sodium alginate polymer phase ensures that the gel has good cohesion; through the synergistic effect of high toughness and strong interfacial force, the gel adhesive is given temperature-responsive bonding properties.
[0026] (3) The present invention forms a green and low-carbon route from the preparation to the use of the gel adhesive, using gelatin and sodium alginate as raw materials. Compared with the preparation of traditional petroleum-based gel adhesives, the present invention has the advantages of easy acquisition of raw materials, simple preparation, environmental friendliness, biocompatibility, and easy degradation. It has potential application prospects in solid-state energy storage systems, flexible wearable materials, biomedical engineering, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:
[0028] Figure 1 3 are microscopic morphology images of the gel prepared in the present invention, wherein a is a three-dimensional tomography image of Example 3, b is a microscopic morphology image of Example 3, c is a microscopic morphology image of Comparative Example 2, and d is an atomic force microscope image of Example 3.
[0029] Figure 2 It is a mechanical property curve diagram in the embodiment of the present invention; wherein a is the stress-strain curve diagram of embodiments 1, 2, and 3, and b is the modulus, stress, and strain bar diagram of embodiments 1, 2, and 3.
[0030] Figure 3 : is the tear energy curve diagram in the embodiment of the present invention; wherein, a is the tear energy curve of embodiment 1, b is the tear energy curve of embodiment 2, c is the tear energy curve of embodiment 3, and d is the tear energy bar graph of embodiments 1, 2, and 3.
[0031] Figure 4 It is a bar graph of the bonding performance in the embodiment of the present invention.
[0032] Figure 5 It is a macroscopic schematic diagram of the temperature-responsive bonding performance of the gel in an embodiment of the present invention. DETAILED DESCRIPTION
[0033] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.
[0034] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0035] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.
[0036] Example 1
[0037] Preparation of gelatin-alginate gel:
[0038] (1) Add 30 g of gelatin into 100 mL of deionized water and place in an oven at 60°C for 2 h to obtain a gelatin solution;
[0039] (2) Add 4 g of sodium alginate to 96 g of deionized water, place the mixture in a 60° C. water bath, and heat and stir for 2 h to obtain a sodium alginate solution.
[0040] (3) Mix the gelatin solution and the sodium alginate solution in a mass ratio of 1:1, stir evenly, pour into a glass mold and place in a refrigerator at 4°C for 1 h to allow it to gel.
[0041] (4) The obtained gel was immersed in a mixed solution of 30 wt% ammonium sulfate and 1 mol / kg lithium sulfate for 12 h, and then immersed in a mixed solution of 30 wt% ammonium sulfate, 1 mol / kg lithium sulfate, and 3 mol / kg zinc acetate for 6 h to obtain gelatin-sodium alginate gel.
[0042] Example 2
[0043] Preparation of gelatin-alginate gel:
[0044] (1) Add 30 g of gelatin into 100 mL of deionized water and place in an oven at 60°C for 2 h to obtain a gelatin solution;
[0045] (2) Add 4 g of sodium alginate to 96 g of deionized water, place the mixture in a 60° C. water bath, and heat and stir for 2 h to obtain a sodium alginate solution.
[0046] (3) Mix the gelatin solution and the sodium alginate solution in a mass ratio of 1:1, stir evenly, pour into a glass mold and place in a refrigerator at 4°C for 1 h to allow it to gel.
[0047] (4) The obtained gel was immersed in a mixed solution of 30 wt% ammonium sulfate and 1 mol / kg lithium sulfate for 12 h, and then immersed in a mixed solution of 30 wt% ammonium sulfate, 1 mol / kg lithium sulfate, and 3 mol / kg zinc acetate for 12 h to obtain gelatin-sodium alginate gel.
[0048] Example 3
[0049] Preparation of gelatin-alginate gel:
[0050] (1) Add 30 g of gelatin into 100 mL of deionized water and place in an oven at 60°C for 2 h to obtain a gelatin solution;
[0051] (2) Add 4 g of sodium alginate to 96 g of deionized water, place the mixture in a 60° C. water bath, and heat and stir for 2 h to obtain a sodium alginate solution.
[0052] (3) Mix the gelatin solution and the sodium alginate solution in a mass ratio of 1:1, stir evenly, pour into a glass mold and place in a refrigerator at 4°C for 1 h to allow it to gel.
[0053] (4) The obtained gel was immersed in a mixed solution of 30 wt% ammonium sulfate and 1 mol / kg lithium sulfate for 12 h, and then immersed in a mixed solution of 30 wt% ammonium sulfate, 1 mol / kg lithium sulfate, and 3 mol / kg zinc acetate for 24 h to obtain a gelatin-sodium alginate gel.
[0054] Microscopic morphology of gelatin-sodium alginate gel Figure 1 , wherein (a) is a three-dimensional tomography image of Example 3, (b) is a microscopic morphology image of Example 3, and (d) is an atomic force microscope image of Example 3. It can be seen that the gel undergoes microphase separation under the synergistic effect of ions, gelatin crystallizes to form crystalline domains, and sodium alginate cross-links to form a polymer phase, which is beneficial to improving the mechanical properties of the gel.
[0055] Example 4
[0056] Preparation of temperature-responsive gelatin-alginate hydrogel:
[0057] (1) Add 30 g of gelatin into 100 mL of deionized water and place in an oven at 60°C for 2 h to obtain a gelatin solution;
[0058] (2) Add 4 g of sodium alginate to 96 g of deionized water, place the mixture in a 60° C. water bath, and heat and stir for 2 h to obtain a sodium alginate solution.
[0059] (3) Mix the gelatin solution and the sodium alginate solution in a mass ratio of 1:1, stir evenly, pour into a glass mold and place in a refrigerator at 4°C for 1 h to allow it to gel.
[0060] (4) The obtained gel was immersed in a mixed solution of 30 wt% ammonium sulfate and 1 M lithium sulfate for 12 h, and then immersed in a mixed solution of 30 wt% ammonium sulfate, 1 mol / kg lithium sulfate, and 3 mol / kg zinc acetate for 24 h. The gel was then heated at 60° C. for 5 min to obtain a gelatin-sodium alginate gel.
[0061] Example 5
[0062] Test of tensile properties of gelatin-sodium alginate gel:
[0063] The tensile properties of gelatin-sodium alginate gel were tested using an electronic universal testing machine.
[0064] The gelatin-sodium alginate hydrogels prepared in the above-mentioned Examples 1, 2 and 3 were cut into strip samples with a length of 5 cm, a width of 1 cm and a thickness of 1.5 mm;
[0065] Then it was fixed between the stretching fixtures and uniaxially stretched in the vertical direction at a stretching rate of 50 mm / min to obtain the tensile stress-strain curve of the gelatin-sodium alginate hydrogel. The results are shown in Figure 2 , wherein a is the stress-strain curve diagram of Examples 1, 2, and 3, and b is the modulus, stress, and strain bar diagram of Examples 1, 2, and 3. It can be seen that the gelatin-sodium alginate gel has good mechanical properties.
[0066] Example 6
[0067] Gelatin-sodium alginate gel tearing energy test:
[0068] The tearing energy of gelatin-sodium alginate gel was tested using an electronic universal testing machine.
[0069] The gelatin-sodium alginate gel prepared in the above-mentioned Examples 1, 2 and 3 was cut into strip samples with a length of 5 cm, a width of 1 cm and a thickness of 1.5 mm, and a 5 mm notch was cut in the middle of the sample;
[0070] Then it was fixed between the stretching fixtures and uniaxially stretched in the vertical direction at a stretching rate of 50 mm / min to obtain the tensile stress-strain curve of the gelatin-sodium alginate gel. The results are shown in Figure 3 , wherein a is the tear energy curve of Example 1, b is the tear energy curve of Example 2, c is the tear energy curve of Example 3, and d is the tear energy bar graph of Examples 1, 2, and 3. It can be seen that the gel prepared by the present invention has better tear energy and bonding strength.
[0071] Example 7
[0072] Test of the bonding properties of gelatin-sodium alginate gel:
[0073] The bonding properties of gelatin-sodium alginate gel were tested using an electronic universal testing machine.
[0074] The gelatin-sodium alginate gel prepared in the above-mentioned Examples 3 and 4 was cut into strips with a length of 2.5 cm, a width of 1 cm, and a thickness of 1.5 mm. The strips were subjected to lap shear tests with zinc sheets and carbon nanotube paper, respectively, to measure the bonding strengths with different materials. The results are shown in FIG. Figure 4 , Figure 5 ,from Figure 4 , 5 It can be seen that the gel prepared in the present invention has a temperature-responsive bonding property, and the bonding strength with the zinc sheet reaches 438 kPa after being heated at 60° C. for 5 minutes.
[0075] Example 8
[0076] Test of gelatin-sodium alginate gel conductivity:
[0077] The conductivity of sodium alginate gel was tested using an electrochemical workstation CHI-660.
[0078] The gelatin-sodium alginate gel samples prepared in the above-mentioned Examples 1, 2 and 3 were cut into block samples with a length of 1 cm, a width of 1 cm and a thickness of 1.5 mm.
[0079] The electrode material is platinum sheet, and the device is assembled in the form of platinum sheet | gel adhesive | platinum sheet. 5 The AC impedance test of the assembled device was carried out in the frequency range of 0.01 Hz to 0.01 Hz and the open circuit voltage was 5 mV, and the conductivity was calculated. The results are shown in Table 1.
[0080] Table 1
[0081] <![CDATA[Conductivity (mScm -1 )]]> Example 1 6.9 Example 2 10 Example 3 13
[0082] Comparative Example 1
[0083] Under the conditions of Example 3, step (4) is modified as follows:
[0084] The obtained gel was immersed in a mixed solution of 30 wt % ammonium sulfate and 1 mol / kg lithium sulfate for 26 h. Other conditions were the same as those in Example 3.
[0085] Comparative Example 2
[0086] Under the conditions of Example 3, step (4) is modified as follows:
[0087] The obtained gel was immersed in a mixed solution of 30 wt % ammonium sulfate, 1 mol / kg lithium sulfate and 3 mol / kg zinc acetate for 26 h to obtain a gelatin-sodium alginate gel. Other conditions were the same as those in Example 3.
[0088] The microscopic morphology of the prepared gel can be found in Figure 1(c) It can be seen that if the mixed salt is used directly, the synergistic effect of the ions is not obvious and no microphase separation occurs, resulting in poor mechanical properties.
[0089] Comparative Example 3
[0090] Under the conditions of Example 3, step (4) is modified as follows:
[0091] The obtained gel was soaked in a mixed solution of 30wt% ammonium sulfate and 1mol / kg lithium sulfate for 12h, and then soaked in a mixed solution of 30wt% ammonium sulfate and 4mol / kg zinc acetate for 24h to obtain gelatin-sodium alginate gel. Other conditions were the same as those in Example 3.
[0092] Comparative Example 4
[0093] Under the conditions of Example 3, step (4) is modified as follows:
[0094] The obtained gel was soaked in a mixed solution of 30wt% ammonium sulfate and 1mol / kg lithium sulfate for 12h, and then soaked in a mixed solution of 30wt% ammonium sulfate and 4mol / kg lithium sulfate for 24h to obtain gelatin-sodium alginate gel. Other conditions were the same as those in Example 3.
[0095] Comparative Example 5
[0096] Under the conditions of Example 3, step (4) is modified as follows:
[0097] The obtained gel was soaked in a mixed solution of 30 wt % ammonium sulfate and 1 mol / kg lithium sulfate for 12 h, and then soaked in a 30 wt % ammonium sulfate solution for 24 h to obtain a gelatin-sodium alginate gel. Other conditions were the same as those in Example 3.
[0098] The tear energy test results are the same as those in Example 6. The tear energy test results are shown in Table 2.
[0099] Table 2
[0100] <![CDATA[Tearing energy (Jm -2 )]]> Example 1 4504.04 Example 2 2607.45 Example 3 6374.67 Comparative Example 1 4302.71 Comparative Example 2 3327.82 Comparative Example 3 2303.25 Comparative Example 4 3980.48 Comparative Example 5 4103.27
[0101] It can be seen that the gel undergoes microphase separation under the synergistic effect of ions, gelatin crystallizes to form crystalline domains, and sodium alginate cross-links to form a polymer phase, which is beneficial to synergistically improve the mechanical properties of the gel.
[0102] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the present invention.
Claims
1. A method for preparing a fully bio-based gel adhesive with temperature-responsive bonding properties, characterized in that: include, The gelatin is heated to obtain a gelatin solution, wherein the mass concentration of the gelatin solution is 20-30%; The sodium alginate is heated and stirred to obtain a sodium alginate solution, wherein the mass concentration of the sodium alginate solution is 2-4%; The gelatin solution and the sodium alginate solution are mixed, the macromolecular chains of the gelatin and the sodium alginate are entangled, and after being stirred evenly, they are poured into a mold and refrigerated to obtain gel I, wherein the mass ratio of the gelatin solution to the sodium alginate solution is 1:0.5~1; The gel I was immersed in a mixed solution of ammonium sulfate and lithium sulfate, and NH4 + 、SO4 2- , Li + The "salting out" effect reduces the solubility of gelatin, causing the gelatin macromolecular chains to aggregate and entangle. During the "salting out" process, water molecules are discharged from the macromolecular chains, and a large number of hydrogen bonds are formed between the gelatin molecular chains, thereby forming crystal domains to obtain gel II, wherein the concentration of ammonium sulfate in the mixed solution of ammonium sulfate and lithium sulfate is 30wt%, the concentration of lithium sulfate is 1mol / kg, and the immersion time is 10-12h; The obtained gel II was immersed in a mixed solution of ammonium sulfate, lithium sulfate and zinc acetate. 2+ Under the action of , a polymer phase is formed through metal coordination, thereby obtaining a gelatin-sodium alginate gel adhesive with gelatin as the crystalline phase and zinc-sodium alginate as the polymer phase, wherein the concentration of ammonium sulfate in the mixed solution of ammonium sulfate, lithium sulfate and zinc acetate is 30wt%, the concentration of lithium sulfate is 1mol / kg, the concentration of zinc acetate is 3mol / kg, and the immersion time is 24h.
2. The preparation method according to claim 1, characterized in that: The mixture is poured into a mold and refrigerated, wherein the refrigeration temperature is 2-4° C. and the gel time is 1-2 hours.
3. The all-biobased gel adhesive with temperature-responsive bonding properties obtained by the preparation method of claim 1 or 2, characterized in that: The gel adhesive can be stretched to 5 times its initial length under uniaxial stretching conditions, and the tear energy can reach 6374.67 J / m 2 It has temperature-responsive bonding properties, and the bonding strength with the zinc sheet reaches 438KPa after heating at 60°C for 5 minutes.
4. Application of the all-biobased gel adhesive according to claim 3 in flexible wearable materials and biomedical engineering.
Citation Information
Patent Citations
Preparation method of multi-network natural polymer physical hydrogel
CN114989454A
Amino modified MXene enhanced gelatin / chitosan composite hydrogel and preparation method thereof
CN115010959A